Outcomes of patients with systemic sclerosis treated with rituximab in contemporary practice: a prospective cohort study. Issue 7 (9th April 2019) - Elhai, Muriel; Boubaya, Marouane; Distler, Oliver; Smith, Vanessa; Matucci-Cerinic, Marco; Alegre Sancho, Juan José; Truchetet, Marie-Elise; Braun-Moscovici, Yolanda; Iannone, Florenzo; Novikov, Pavel I; Lescoat, Alain; Siegert, Elise; et al.
Abstract : Objective: To assess the safety and efficacy of rituximab in systemic sclerosis (SSc) in clinical practice. Methods: We performed a prospective study including patients with SSc from the European Scleroderma Trials and Research (EUSTAR) network treated with rituximab and matched with untreated patients with SSc. The main outcomes measures were adverse events, skin fibrosis improvement, lung fibrosis worsening and steroids use among propensity score-matched patients treated or not with rituximab. Results: 254 patients were treated with rituximab, in 58% for lung and in 32% for skin involvement. After a median follow-up of 2 years, about 70% of the patients had no side effect. Comparison of treated patients with 9575 propensity-score matched patients showed that patients treated with rituximab were more likely to have skin fibrosis improvement (22.7 vs 14.03 events per 100 person-years; OR: 2.79 [1.47–5.32]; p=0.002). Treated patients did not have significantly different rates of decrease in forced vital capacity (FVC)>10% (OR: 1.03 [0.55–1.94]; p=0.93) nor in carbon monoxide diffusing capacity (DLCO) decrease. Patients having received rituximab were more prone to stop or decrease steroids (OR: 2.34 [1.56–3.53], p<0.0001). Patients treated concomitantly with mycophenolate mofetil had a trend for better outcomes as compared with patients receiving rituximab alone (delta FVC: 5.22 [0.83–9.62]; p=0.019 as compared with controls vs 3 [0.66–5.35]; p=0.012). Conclusion: Rituximab use was associated with a good safety profile in this large SSc-cohort. Significant change was observed on skin fibrosis, but not on lung. However, the limitation is the observational design. The potential stabilisation of lung fibrosis by rituximab has to be addressed by a randomised trial.